Mind-Travelling and Voyage Drama in Early Modern England - McInnis, D. author. aut Link
XIII, 236 p.
Keywords: Drawing on a wide range of drama from across the seventeenth century, including works by Marlowe, Heywood, Jonson, Brome, Davenant, Dryden and Behn, this book situates voyage drama in its historical and intellectual context between the individual act of reading in early modern England and the communal act of modern sightseeing.